Studies on the protein-synthesizing activity of the ribosomes of rat liver. The activity of free polysomes - Campbell, P. N. (1965)
1. The activities of microsome fractions from the liver of adult and 5-day-old rats for the incorporation of [(14)C]phenylalanine into protein were similar in the presence and absence of polyuridylic acid. 2. The activity of a light-microsome fraction from adult liver was greater than that of a heavy-microsome fraction, and the light-microsome fraction was also more markedly stimulated by the presence of polyuridylic acid. 3. The light-microsome fraction, when analysed by density-gradient centrifugation, contained a higher ratio of free ribosomes to bound ribosomes, whereas the reverse was true for the heavy-microsome fraction. Similar results were obtained for liver from adult and 5-day-old rats. 4. When the light-microsome fraction was incubated under conditions in which amino acid was incorporated into protein there was only a small increase in the ratio of free to bound ribosomes. When such a fraction was incubated with [(14)C]leucine and was then subjected to density-gradient centrifugation the fraction with the highest specific activity based on RNA had a density between that of the bound and free ribosomes. Treatment of the incubated fraction with ribonuclease shifted the radioactivity towards the free ribosome peak. These properties are consistent with the presence of active free polysomes. Such a component appeared also to be present when the heavy-microsome fraction was incubated under similar conditions. 5. The effect of the presence of polyuridylic acid on the incorporation of [(14)C]phenylalanine by the light-microsome fractions from liver of adult and 5-day-old rats was greatest in the region of the free ribosomes, but it is probable that some small polysomes containing polyuridylic acid are formed. 6. Polyuridylic acid also stimulated the bound ribosomes to a small extent when the heavy-microsome fraction from the liver of young rats was incubated with [(14)C]phenylalanine. 7. The results are discussed in terms of the various morphological constituents in liver now known to play a role in the synthesis of protein for export and for the internal activity of the cell.